2022
DOI: 10.3171/2021.3.jns204378
|View full text |Cite
|
Sign up to set email alerts
|

Visual deterioration after endonasal endoscopic skull base surgery: causes, treatments, and outcomes

Abstract: OBJECTIVE Visual deterioration after endoscopic endonasal transsphenoidal surgery (EETS) for sellar and parasellar masses is a rare but serious complication caused by either compressive or ischemic mechanisms. Timely diagnosis and intervention may restore vision if instituted appropriately. The associated risk factors and their relation to the success of intervention are not well understood. METHODS The authors examined a series of 1200 consecutive EETS cases performed by the senior author at Weill Cornell/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This study is limited by its retrospective nature. Although this data set's prevalence of apoplexy and SPH are concordant with the existing literature, [5][6][7][8][20][21][22] the small number of cases makes assessment of long-term outcomes more challenging. Specifically, although there were no mortalities in our cohort, other recent studies have found that up to 42% of SPH cases may be fatal.…”
Section: Limitations and Generalizabilitysupporting
confidence: 79%
See 1 more Smart Citation
“…This study is limited by its retrospective nature. Although this data set's prevalence of apoplexy and SPH are concordant with the existing literature, [5][6][7][8][20][21][22] the small number of cases makes assessment of long-term outcomes more challenging. Specifically, although there were no mortalities in our cohort, other recent studies have found that up to 42% of SPH cases may be fatal.…”
Section: Limitations and Generalizabilitysupporting
confidence: 79%
“…[2][3][4] The rate of SPH after endonasal resection of pituitary neuroendocrine tumor ranges between 0.1% and 1.5, and composes 7.4% of 30-day readmissions for PitNET surgery. [5][6][7][8][9][10][11] Although this is similar to the rate in the broader neurosurgical population, 12 the specific risk factors for developing SPH after pituitary surgery are unknown and potentially unique. This topic has not been investigated thoroughly because of the low incidence of SPH, 13 and as a result, recommendations for prevention and surveillance are lacking.…”
mentioning
confidence: 76%
“…Carnevale et al reported that visual deterioration caused by optic nerve compression or ischemia after EEA is rare but treatable. 52 ) We encountered two cases of delayed postoperative visual deterioration (one after EEA and the other after SFA). Although the etiology is unclear, vasospasm of small arteries, such as the SHAs or other chiasmatic branches of the circle of Willis, may be responsible.…”
Section: Discussionmentioning
confidence: 99%